Jüdinnen - Literarische Weiblichkeitsentwürfe im 20. Jahrhundert - Ludewig, Anna-Dorothea (Europäisch-jüdische Studien - Beiträge, 2022)
In the nineteenth and, in particular, twentieth centuries, literature became a place to negotiate ideas of Jewish femininity, an experimental space in which contemporary discourses were carried out and tried out on and using female Jewish characters. Literary portrayals of Jewish women and therefore Jewish femininity as a paradigm of male authorship are thus at the center of this study.